Servant Leadership and Its Relationship with Job Satisfaction at Daarul Qur'an Kalibata Elementary School - Hani Islami (al-Afkar, Journal For Islamic Studies, 2026)
The main objective of this study is to explore the relationship between job satisfaction at SD Daarul Qur'an Kalibata and the concept of servant leadership. Servant leadership is a method of leading that focuses on providing service to others, particularly team members, with the aim of enhancing their well-being and development. In an educational context, servant leadership can have a major impact on the motivation and job satisfaction of teachers and staff. In turn, job satisfaction is employees' positive feelings towards their jobs, which can affect their commitment and performance. The effect of servant leadership on job satisfaction at SD Daarul Qur'an Kalibata was studied through a qualitative case study. Data were collected through observations of school leadership practices and thorough interviews with the principal, teachers and administrative staff. Thematic analysis was the data analysis method used, which allowed the researcher to find important patterns in the relationship between job satisfaction and servant leadership. The results showed that managing servants well at SD Daarul Qur'an Kalibata increased their job satisfaction. The research participants said that the school leaders increased their motivation and comfort while working. The main factors that increased job satisfaction were open communication, empathy, and empowerment in decision-making. This study found that increasing employee satisfaction in the workplace can be achieved by using servant leadership, particularly at SD Daarul Qur'an Kalibata.